Mechanical effects of cell size and wall thickness on the rubber wood honeycomb sandwich composites - Tan, Teng Teng (2022)
Malaysia has one of the biggest rubber wood plantations to meet the latex demand from worldwide where rubber trees are utilised in the furniture industry. Due to high volume of residue produced from processing the wood, sawdust and wood flour are processed into so called green wood plastic composite products such as medium density fibreboard (MDF) and particle board. In this research, it is aimed to optimise the applications of solid rubber wood as a structural member in the form of sandwich composite. It deserves more significant role in the engineering field apart from furniture industry to decrease the dependency on synthetic woods. It opens up a new economy source for the rubber wood. This also associates with the research trend to promote green and biodegradable natural material. However, geometrical parameters on rubber wood (eg. cell wall thickness and cell size) have not been discussed previously that determine the mechanical performance of the sandwich composites by using natural solid wood and its failure mode in terms of adhesion behaviour between the facesheet and its honeycomb. Hand lay-up technique assisted by vacuum bagging technique at room temperature carried out for a rubber wood based honeycomb composites with two layers of glass fibre facesheets on each side was fabricated with 1mm, 1.5mm, 2mm and 3mm cell wall. Meanwhile, the cell size of core was 7mm, 7.5mm, 8mm and 9 mm with a standard core height of 10mm. In order to verify such geometrical parameters on rubber wood, it was tested with composites using pine and balsa wood core. Tests carried out were flexural test (ASTM C393), compression test (ASTM C365), flatwise tensile test (ASTM C297) and climbing drum peel (ASTM D1781). By increasing the cell wall thickness, the flexural performance increase by 12.32% (rubber wood), 43.60% (pine) and 113.98% (balsa) from 1mm to 3mm as well as increase of 11% (rubber wood), 18% (pine) and 38% (balsa) in flatwise compression. Rubber wood composites with 3mm cell wall improve by 17.41% in flatwise tensile and only 1% difference in climbing drum peel test (with reduced density in honeycomb structure) when compared with SWWS. With the increase in cell size from 7mm to 9mm, the flexural properties dropped 18.36% (rubber wood), 41.14% (pine) and 10.20% (balsa) while the flatwise compression properties dropped 22.26% (rubber wood), 30.68% (pine) but increased 97.91% for balsa. Using rubber wood honeycomb from 7mm to 9mm, the flatwise tensile properties dropped 30.41% and 38.42% (compared with SWWS) in climbing drum peel test. This research has addressed the research gap on the feasibility of using rubber wood as the natural core in honeycomb composite as a structural member that serves as an alternative to synthetic wood plastic composites for greener environment. The geometrical parameters are suitable for wood core materials in hardwood and softwood categories. As such, it has successfully utilised RWC7W3 in developing a new platform as a prototype for electric scooter.